2015
DOI: 10.1186/s12906-015-0517-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tai Chi on mononuclear cell functions in patients with non-small cell lung cancer

Abstract: BackgroundTai Chi is the Chinese traditional medicine exercise for mind-body health. The objective of this study is to investigate the effect of Tai Chi Chuan (TCC) exercise on the proliferative and cytolytic/tumoricidal activities of peripheral blood mononuclear cells (PBMCs) in postsurgical non-small cell lung cancer (NSCLC) patients.MethodsPatients (n = 27) were randomly divided into the control group (n = 13) and the TCC group (n = 14). TCC group participated in Tai Chi 24-type exercise for 16 weeks, 60-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 39 publications
(43 reference statements)
0
39
0
1
Order By: Relevance
“…Long-term home-based, moderate-intensity walking was a feasible and effective intervention for managing anxiety and depression among patients with LC 267 . Long-term Tai Chi helped to improve the proliferation and cell-dissolving activity of peripheral blood mononuclear cells in patients, 268 it decrease body fatigue and physical fatigue, and it increased the vitality of patients 269 . After receiving supervised CT, the patients’ pain was decreased, but no improvement in HRQoL 270 .…”
Section: Resultsmentioning
confidence: 99%
“…Long-term home-based, moderate-intensity walking was a feasible and effective intervention for managing anxiety and depression among patients with LC 267 . Long-term Tai Chi helped to improve the proliferation and cell-dissolving activity of peripheral blood mononuclear cells in patients, 268 it decrease body fatigue and physical fatigue, and it increased the vitality of patients 269 . After receiving supervised CT, the patients’ pain was decreased, but no improvement in HRQoL 270 .…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective randomized study in postsurgical patients with NSCLC, 16 weeks of tai chi chuan training was demonstrated to significantly promote proliferation of peripheral blood mononuclear cells, as compared with both basal levels ( p < .001) and a control group ( p < .05), with an increase in their cytotoxicity demonstrated by incubation with lung adenocarcinoma A549 cells ( p < .001). Moreover, a relevant increase in circulating NK cell percentage, natural killer T, and dendritic CD11c cells between the exercise and control groups was detected . In another prospective randomized trial, the control group, including 16 patients with surgically resected NSCLC, experienced a decrease in ratio of IFN‐γ–producing CD3+ T lymphocytes (T1) to IL‐4–producing CD3+ T lymphocytes (T2) and an increase in cortisol levels during recovery time.…”
Section: Biological Mechanismsmentioning
confidence: 96%
“…Reasons and purposes for using CAM include longer survival, prevention of cancer recurrence, and improvement of immune function. 31 Other reasons include alleviation of side-effects from conventional treatment, meeting unmet physical needs, managing emotional distress, and improving QOL. 7 , 18 , 19 , 32 , 33 However, the actual efficacy of CAM use in meeting such purposes has not been adequately assessed.…”
Section: Introductionmentioning
confidence: 99%